2006
DOI: 10.1148/rg.26si065503
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted MR Imaging of Early-Stage Creutzfeldt-Jakob Disease: Typical and Atypical Manifestations

Abstract: Creutzfeldt-Jakob disease causes progressive dementia and, eventually, death. The infectious agent is thought to be proteinaceous scrapie particles. Prompt diagnosis is essential to prevent human-to-human transmission. Progressive brain atrophy and areas of high signal intensity in the cerebral cortex and basal ganglia are well-known features of Creutzfeldt-Jakob disease depicted on T2-weighted magnetic resonance (MR) images. However, in the early stage of disease, the appearance of the brain on T2-weighted MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 39 publications
1
35
0
5
Order By: Relevance
“…Case reports have previously described unilateral signal-intensity abnormalities in MR imaging of patients with CJD, but studies with larger samples consistently showed bilateral involvement. [24][25][26][27][28][29][30][31] In the current study, we have confirmed bilaterally reduced ADC in the putamen at b ϭ 1000 s/mm 2 with a more liberal statistical significance level (P Ͻ .005). We believe the absence of bilateral findings in the putamen at b ϭ 1000 s/mm 2 merely reflects its lower statistical power.…”
Section: Discussionsupporting
confidence: 74%
“…Case reports have previously described unilateral signal-intensity abnormalities in MR imaging of patients with CJD, but studies with larger samples consistently showed bilateral involvement. [24][25][26][27][28][29][30][31] In the current study, we have confirmed bilaterally reduced ADC in the putamen at b ϭ 1000 s/mm 2 with a more liberal statistical significance level (P Ͻ .005). We believe the absence of bilateral findings in the putamen at b ϭ 1000 s/mm 2 merely reflects its lower statistical power.…”
Section: Discussionsupporting
confidence: 74%
“…Gadolinium administration may be a helpful adjunct in this circumstance because enhancement is reported in Wernicke's encephalopathy whereas it is not a feature of CJD. Finally, an underrecognized cause of rapidly progressive but potentially reversible dementia is venous congestive encephalopathy secondary to dural arteriovenous malformation (16,97). In our experience, restricted diffusion is uncommonly seen, but venous hypertension may result in different pattern of parenchymal edema.…”
Section: Differential Diagnosismentioning
confidence: 58%
“…However, these reports have the potential of being flawed by the time delay between the imaging and autopsy, especially given the fact that the histological changes are known to evolve spatially over time. Indeed, DWI findings may become less conspicuous in the terminal stage of the disease and may even normalize (8,(16)(17)(18). This evolution may be related to increased gliosis, producing increased water diffusivity, thus balancing the restricted diffusion seen earlier in the disease (11,19).…”
Section: Neuroimagingmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 In the much less common Japanese encephalitis, these abnormalities tend to be seen in subcortical gray matter regions. 13 Patchy enhancement with gadolinium administration indicates nonspecific inflammatory changes generally seen in encephalitis.…”
Section: Infection-related Etiologiesmentioning
confidence: 99%